Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1093/ofid/ofv159
|View full text |Cite
|
Sign up to set email alerts
|

Low Concordance With Guidelines for Treatment of Acute Cystitis in Primary Care

Abstract: We found low concordance with the updated 2010 IDSA guidelines for both the choice of drug and duration of therapy for acute cystitis. Interventions to decrease overuse of fluoroquinolones are needed to preserve the antimicrobial efficacy of these important antimicrobials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
69
1
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(83 citation statements)
references
References 37 publications
6
69
1
2
Order By: Relevance
“…[6] Adherence to guidelines in primary care has been shown to vary significantly depending on the condition being treated. [7][8][9][10][11][12][13] Studies have shown poor guideline adherence for respiratory problems, [7][8][9][10] urinary tract infections, [11,12] tonsillitis [13] and acute diarrhoea. [10] Other variables associated with poor adherence include seniority of the clinician, [14] prescriber workload, [15] patient age [8,14] and area-level socioeconomic status.…”
Section: Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…[6] Adherence to guidelines in primary care has been shown to vary significantly depending on the condition being treated. [7][8][9][10][11][12][13] Studies have shown poor guideline adherence for respiratory problems, [7][8][9][10] urinary tract infections, [11,12] tonsillitis [13] and acute diarrhoea. [10] Other variables associated with poor adherence include seniority of the clinician, [14] prescriber workload, [15] patient age [8,14] and area-level socioeconomic status.…”
Section: Researchmentioning
confidence: 99%
“…One study showed that 82% of trimethoprim prescriptions, 73% of nitrofurantoin prescriptions and 71% of fluoroquinolone prescriptions for UTIs were prescribed for longer periods than guidelines recommended. [11] For patients with respiratory problems, only 34.1% of cases were adherent to guidelines. Of those that were not adherent, 48.3% of the errors were because the antibiotic was not required (Fig.…”
Section: Physiological System and Type Of Antibioticmentioning
confidence: 99%
“…Ciprofloxacin and levofloxacin were prescribed for 3 days in 29.0% of patients only; a similar situation was observed for trimethoprim/ sulphamethoxazole which was prescribed for 3 days in only 16% of patients, and nitrofurantoin, administered for 3 days in 14% of cases only. 29 The most concerning aspects were the first-line use of fluoroquinolones and the long-term administration of all the antibiotics for the management of uncomplicated UTIs.…”
Section: Asymptomatic Bacteriuriamentioning
confidence: 99%
“…In addition to improving patient outcomes, increased concordance with guidelines could support more rational antibiotic prescribing, thereby helping to mitigate antimicrobial resistance . Australian studies have evaluated the level of concordance between antibiotic therapy prescribed for hospital inpatients and recommendations in Therapeutic Guidelines .…”
Section: Introductionmentioning
confidence: 99%